PENGEMBANGAN SISTEM TEMU KEMBALI INFORMASI DIGITAL FULLTEXT ARTIKEL JURNAL DI PDII – LIPI - Afandi, Sjaeful; Ardiansyah, Firman; Soedarsono, Blasius (BACA: Jurnal Dokumentasi dan Informasi, 2015)
One of the tasks in Center for Scientific Documentation and Information – Indonesian Institutes of Sciences (PDII - LIPI) is to disseminate the results of existing research in Indonesia. The research result can be either books or journal articles. Currently, activity of retrieval system on a journal article have still using a traditional retrieve systems regardless of the relevance of data search results. The order of search results based only on the order of data entry that need to be developed information retrieval of digital full text articles as data retrieval alternative. Development of information retrieval system that uses Sphinx Search software. The data used are the result of the conversion from Portable Digital Format (PDF) into XML as much as 1000 file. Data of conversion result, then are processed through “tokenisasi” and indexing techniques using Sphinx Search software. Retrieval system tested with a query that has been determined. Retrieval results calculated using standard recalls eleven that in mind the relevance and accuracy. Data retrieval system produces search results that are relevant and accurate with average presicion (AVP) value is of 79%.